Paramedic Perspectives on Barriers to Prehospital Acute Stroke Recognition. (3rd May 2016) - Hodell, Evan; Hughes, Shana D.; Corry, Megan; Kivlehan, Sean; Resler, Brian; Sheon, Nicolas; Govindarajan, Prasanthi
ABSTRACT: Background: Emergency Medical Service (EMS) providers are tasked with rapid evaluation, stabilization, recognition, and transport of acute stroke patients. Although prehospital stroke scales were developed to assist with stroke recognition, unrecognized challenges exist in the prehospital setting that hinder accurate assessment of stroke. The goal of this qualitative study was to systematically understand the challenges and barriers faced by paramedics in recognizing stroke presentations in the field.Methods: Paramedics from 12 EMS agencies serving a mix of rural, suburban, and urban communities in the State of California participated in five focus group discussions. Group size ranged from 3–8, with a total of 28 participants. Demographics of the participants were collected and focus group recordings were transcribed verbatim. Transcripts were subjected to deductive and inductive coding, which identified recurrent and divergent themes.Results: Strong consensus existed around constraints to prehospital stroke recognition; participants cited the diversity of stroke presentations, linguistic diversity, and exam confounded by alcohol and or drug use as barriers to initial evaluation. Also, lack of educational feedback from hospital staff and physicians and continuing medical education on stroke were reported as major deterrents to enhancing their diagnostic acumen. Across groups, participants reported attempting to foster relationships with hospital personnel to augment their educational needs, but this was easier for rural than urban providers.Conclusions: While challenges to stroke recognition in the field were slightly different for rural and urban EMS, participants concurred that timely, systematic feedback on individual patients and case-based training would strengthen early stroke recognition skills.